Karakteristik Struktur Morfologi Ikan Gatul Betina Di Sungai Kendedes-Malang Sebagai “Candidate Animal Model” Dibidang Biologi Perkembangan - Vanda Aprinia Edfaniar; Benedictus Renaldi Ncemar; Winda Krisnawati; Nikmatul Iza (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
Gatul fish (Poecilia sp.) is included in the family Poeciliidae which is a small fish. This fish has the ability to breed very quickly, so the population of Gatul fish (Poecilia sp.) is very abundant. The purpose of this study was to determine the morphological characteristics of female Gatul fish in the Kendedes-Malang river as a "candidate animal model" in the field of developmental biology. This type of research is an exploratory descriptive study with a qualitative approach to identify the morphological characteristics of female Gatul fish in the Kendedes-Singosari river. Characteristics of morphological structure data were analyzed descriptively including body length measurements of female Gatul fish, observations of fins, type of scales, and pigmentation (color patterns). Based on observations, it is known that the female Gatul fish has a large body shape with a rounded belly. The caudal fin (tail) of Gatul fish has a round shape. The type of scales in Gatul fish is cycloid. The body of the female fish has melanocytes which give a clear, slightly blackish color almost all over the body to the fins.